ClinVar Is a Critical Resource to Advance Variant Interpretation. (4th December 2017) - Rehm, Heidi L.; Harrison, Steven M.; Martin, Christa L.
Abstract : In this Letter to the Editor, potentially flawed conclusions of a recent study are discussed.